คำถามและพลังของการกล่าวถ้อยในหนังเรื่องวิคตอเรียแอนด์อับดุล: Questioning and Illocutionary Force in Victoria and Abdul Movie - นุศาสตร์เลิศ อนงค์นาฏ (Journal of Humanities and Social Sciences (HUSOKKU), 2025)
Abstract This article examines the main character Abdul’s use of questioning in Victoria & Abdul when communicating to listeners of different social statuses. Although questioning is recognized as a universal practice, it is culturally specific depending on social factors. This study aims to analyze the questioning and illocutionary force of a lower-class speaker toward hearers of different social status as depicted in a British royal historical film based on a true story, Victoria and Abdul. The data were collected from a 17,257-word or 716-token film script obtained from a public website. The framework of Cruse was used as a model in this study to analyze illocutionary meaning. The findings revealed that Yes/No questions were used more frequently than Wh-questions. The main character used Yes/No questions for permission/requesting, confirming or refuting, confirming or refuting for more information, inviting, and expressing empathy. For Wh-questions, the research revealed that the character Abdul used this type of question for asking for more information, thanking, and complaining. Moreover, the research findings also indicated that illocutionary forces varied depending on different statuses of the hearers as reflected in some of the subtypes of illocutionary force found in some utterances directed toward hearers of certain statuses. This research contributes to the field of pragmatics by analyzing communication between people of different social statuses. This new finding contributes to the understanding of how social status influences questioning strategies and illocutionary force within the cinematic context.